Cerebrospinal fluid leak post COVID-19 nasopharyngeal swab for a patient with idiopathic intracranial hypertension: a case report. Issue 10 (28th October 2021) - Asiri, Mohammed; Alhedaithy, Riyadh; Alnazer, Zainab
Abstract: Coronavirus disease 2019 caused by severe acute respiratory syndrome coronavirus 2 is an infectious disease that led to a global pandemic. In this article, we reported a case of a young women who is known to have idiopathic intracranial hypertension, with iatrogenic skull base injury from a nasopharyngeal swab. Her case was complicated by meningitis.